𝒞1, β regularity for Dirichlet problems associated to fully nonlinear degenerate elliptic equations. (13th August 2014) - Birindelli, I.; Demengel, F.
Abstract : We prove Hölder regularity of the gradient, up to the boundary for solutions of some fully-nonlinear, degenerate elliptic equations, with degeneracy coming from the gradient.